Synthesis of Tetravalent Thio- and Selenogalactoside-Presenting Galactoclusters and Their Interactions with Bacterial Lectin PA-IL from Pseudomonas aeruginosa - Illyés, Tünde Zita; Malinovská, Lenka; Rőth, Erzsébet; Tóth, Boglárka; Farkas, Bence; Korsák, Marek; Wimmerová, Michaela; Kövér, Katalin E; Csávás, Magdolna (Molecules (Basel, Switzerland), 2021)
Synthesis of tetravalent thio- and selenogalactopyranoside-containing glycoclusters using azide-alkyne click strategy is presented. Prepared compounds are potential ligands of Pseudomonas aeruginosa lectin PA-IL. P. aeruginosa is an opportunistic human pathogen associated with cystic fibrosis, and PA-IL is one of its virulence factors. The interactions of PA-IL and tetravalent glycoconjugates were investigated using hemagglutination inhibition assay and compared with mono- and divalent galactosides (propargyl 1-thio- and 1-seleno-β-d-galactopyranoside, digalactosyl diselenide and digalactosyl disulfide). The lectin-carbohydrate interactions were also studied by saturation transfer difference NMR technique. Both thio- and seleno-tetravalent glycoconjugates were able to inhibit PA-IL significantly better than simple d-galactose or their intermediate compounds from the synthesis.
Keywords: Bacterial Proteins; multivalency; Glycoconjugates; Lectins; lektiny; Humans; PA-IL lectin; glykokonjugáty; selenoglycosides; lidé; galactoclusters; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; bakteriální proteiny; Pseudomonas aeruginosa